PD-L1 immunohistochemical expression considering HPV status in oropharyngeal squamous cell carcinoma - dos Anjos, Raíssa Soares (2024)
This systematic review aims to determine whether the presence of human papillomavirus (HPV) influences the immunohistochemical expression of programmed cell death-1 ligand (PD-L1) in oropharyngeal squamous cell carcinoma (OPSCC). PD-L1 immunohistochemical expression varies in OPSCC, and the presence of HPV is a plausible explanation for this variability. Comprehending these findings is crucial, as high PD-L1 expression in the tumor microenvironment of OPSCC can help identify patient subgroups that could be suitable for immunotherapy. Therefore, a systematic review was conducted following PRISMA guidelines (CRD42023437800). An electronic literature search was performed without time or language restrictions. The search included PubMed/MEDLINE, Embase, Scopus, Web of Science, https://clinictrials.gov, and relevant journals. A meta-analysis was performed using RStudio. Fourteen studies involving 1,629 participants were included. The sample consisted predominantly of males (81.26%) with a mean age of 58.3 years. Concerning clinical and pathological characteristics, the most frequently described anatomical location was the tonsils (68.54%), and most participants were either current or former smokers (78%) and alcohol users (79%). Advanced TNM IV was the most common stage. Regarding histopathological characteristics, HPV 16 was the only type mentioned, and half of the cases were detected through immunohistochemistry. The SP142 clone (35.7%) and the pattern of membrane immunostaining in tumor cells (71%) were the most commonly employed methods. The most prevalent findings were positive expression of PD-L1 (64.28%) and negative HPV status (57.14%). The association between PD-L1 positivity and HPV positivity (78.57%) was confirmed by meta-analysis. The conclusion was that HPV-positive status has an impact on immunohistochemical expression of PD-L1 in OPSCC.